PEMBERDAYAAN MASYARAKAT MENJAGA TUMBUH KEMBANG ANAK MELALUI PRODUK OLAHAN MAKANAN PADAT GIZI PADA KELOMPOK MITRA DESA PADDINGING KECAMATAN SANROBONE KABUPATEN TAKALAR - Arif, Muhammad; Suriyanti, Suriyanti; Zafira, Zahra; Wahyuni, Nur (Arunika: Jurnal Pengabdian Masyarakat, 2022)
: Indonesia is one of the countries that has the world's marine biodiversity, including seaweed or algae. Among the many cultivated seaweeds in Indonesia are Gracilla sp & Kappaphycus cottonii (eucheuma cottonii). Economically, seaweed is a potential commodity to be developed because of the nutritional value it contains. Seaweed can be processed into processed food or snacks such as jelly, there are also those who process Seaweed (Nori) as medicinal and cosmetic products. Seaweed is also used in the pharmaceutical, textile and other industries. The advantages that can be obtained in cultivating seaweed include reducing the number of unemployed, increasing people's income, and increasing local revenue (PAD). Social aspect, the development of Seaweed cultivation business provides benefits for the community around the cultivation location. With this cultivation business, it is hoped that it will be able to meet broad market needs and be able to foster work enthusiasm and entrepreneurial spirit in the local community. From a health perspective, consuming seaweed can help maintain or lose weight, help speed up wound healing, strengthen bones and teeth, improve the digestive system, increase energy, good for people with diabetes and cholesterol, avoid swelling of the thyroid gland, fight disease, and can slow the spread of cancer cells.